Performance and economic evaluation of Melia composita and Emblica officinalis based agroforestry models in Haridwar and SAS Nagar districts - Singh, Rambir; Singh, Charan; Gulati, Ajay (Indian Journal of Agroforestry, 2020)
Present study is the outcome of performance and economic evaluation of Melia composita (melia) and Emblica officinalis (aonla) based agroforestry models in Haridwar (Uttarakhand) and Sahibzada Ajit Singh Nagar (Punjab). M. composita and E. officinalis based agroforestry models were established in randomized block design at 6 m Ã— 4 m with Rauvolfia serpentina (sarpgandha) and Withania somnifera (ashwagandha) as intercrop (spacing 60 cm Ã— 60 cm) along with seasonal agriculture crops like Lens culinaris (masoor) and Arachis hypogaea (groundnut). Ashwagandha and sarpgandha are well suitable and synchronized with both melia and aonla without releasing any negative effect on tree as well as agriculture crops. The expected B: C ratio in eight years rotation was found to be maximum (2.75) in model-2 (aonla-sarpgandha-masoor), followed by model-1 (melia-sarpgandha-masoor) (2.66), model-4 (aonla-ashwagandha-groundnut-mustard) (2.47) and model-3 (melia-ashwagandha-groundnut-wheat) (2.36), respectively. As per net returns and B: C ratio, model-2 (aonla-sarpgandha-masoor) was found more economic to other models in expected eight years rotation.